2000
DOI: 10.1007/s002030000220
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of coupling products formed by biotransformation of biphenyl and diphenyl ether by the white rot fungus Pycnoporus cinnabarinus

Abstract: Cells of the white rot fungus Pycnoporus cinnabarinus grown in glucose were able to hydroxylate biphenyl and diphenyl ether, although growth was inhibited by these substrates at concentrations above 250 microM. 2- and 4-Hydroxybiphenyl were detected as products of biphenyl metabolism and 2- and 4-hydroxydiphenyl ether as products of diphenyl ether metabolism in the culture media. After addition of 2-hydroxydiphenyl ether and 2-hydroxybiphenyl to cell-free supernatants containing laccase as the only ligninolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Laccase oxidative coupling reactions involving different types of soluble molecules to lignin or lignin model substrates has previously been described for wood based materials [16,21]. In our previous mechanistic studies, the use of defined model substrates revealed that both 5-5 and 4-O-5 coupling reactions were possible [16,[21][22][23] and this can be used to explain the couplings in this study.…”
Section: Resultssupporting
confidence: 62%
“…Laccase oxidative coupling reactions involving different types of soluble molecules to lignin or lignin model substrates has previously been described for wood based materials [16,21]. In our previous mechanistic studies, the use of defined model substrates revealed that both 5-5 and 4-O-5 coupling reactions were possible [16,[21][22][23] and this can be used to explain the couplings in this study.…”
Section: Resultssupporting
confidence: 62%
“…However, the involvement of laccase should be assumed because of its presence in many fungal taxa capable of degrading similar aromatic structures. Laccase of the white rot fungi, Trametes versicolor and Pycnoporus cinnabarinus, was shown to transform 2-hyxroxyDF 96) . P. cinnabarinus laccase was reported to be capable of dehalogenating chlori-nated hydroxybiphenyls 167) .…”
Section: )mentioning
confidence: 99%
“…Also, dimerization, oligomerization, and polymerization of phenolic compounds can be obtained 8 . This enzyme has been used to synthesize hydroxybiphenyl dimers 14 , isoeugenol dimers 15 , and ferulic acid dimers 16 . Laccase is also able to couple a laccase substrate with a non-laccase substrate (known as a mediator) to create new molecules (heterodimers) 8,17 .…”
Section: Introductionmentioning
confidence: 99%